(untitled) (Medico Legal Update, 2020)
Purpose: To evaluate the efficacy of nurse assisted distraction strategies on postoperative pain, parent pain catastrophizing, mother and child anxiety and physiological parameters. Method: The present study included a total of 160 mother-child dyads (2-7 years) inpatient to paediatric surgical unit. The study participants are randomized into intervention and control group. The intervention group will receive age appropriate NADS along with the standard care for three postoperative days and the control group will receive only standard care. The participants will be followed from day of admission to postoperative day 3. Results: NADS will be delivered for three postoperative days to the children in the postoperative unit. Children received intervention had shown improvement in the postoperative pain and anxiety in these three postoperative days. Conclusion: The findings of the study will empower nurses and health care professionals to practice distraction strategies in the postoperative unit which will decrease postoperative pain, anxiety and reduces the dosage of analgesics among children